2019
DOI: 10.3748/wjg.v25.i13.1580
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNAs as potential new biomarkers for early detection of early gastric cancer

Abstract: BACKGROUND Early gastric cancer (EGC), compared with advanced gastric cancer (AGC), has a higher 5-year survival rate. However, due to the lack of typical symptoms and the difficulty in diagnosing EGC, no effective biomarkers exist for the detection of EGC, and gastroscopy is the only detection method. AIM To provide new biomarkers with high specificity and sensitivity through analyzed the differentially expressed microRNAs (miRNAs) in EGC and AGC and compared them with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…MiR-1180-3p was suggested to be one essential plasma biomarker to distinguish gastric cancer from benign gastritis, and to distinguish early gastric cancer from advanced gastric cancer [ 33 ]. This miRNA was also used to discriminate hepatocellular carcinoma (HCC) occurrence after direct antiviral therapy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1180-3p was suggested to be one essential plasma biomarker to distinguish gastric cancer from benign gastritis, and to distinguish early gastric cancer from advanced gastric cancer [ 33 ]. This miRNA was also used to discriminate hepatocellular carcinoma (HCC) occurrence after direct antiviral therapy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al [59] found increased plasma levels of miR-221, miR-20a, and miR-106b in GC patients compared to normal controls. Zhu et al [60] identified the combination of miR-425-5p, miR-1180-3p, miR-122-5p, miR-24-3p, and miR-4632-5p as a new potential biomarker panel, suggesting to combine gastroscopy with this signature to improve early GC detection. miR-21 levels, in both serum and peripheral blood mononuclear cells, were increased in GC patients compared to controls and could be used in the diagnosis of early (stage I) and late (stage IV) GC [61] .…”
Section: Gastric Cancermentioning
confidence: 99%
“…And the combination of serum miR-24-3p and AFP (alpha fetoprotein) could improve the diagnostic accuracy for HCC, compared to each biomarker alone. Zhu et al ( 33 ) reported that the differentially expressed circulatory plasma miR-24-3p together with miR-425-5p, miR-1180-3p, miR-122-5p, and miR-4632-5p could be considered as a novel potential biomarker panel for the diagnosis of early gastric cancer. Fang et al ( 60 ) identified a panel of plasma miRNAs, including miR-24, could be a helpful diagnostic marker for colorectal carcinoma detection, especially for its early stage.…”
Section: Therapeutic Relevance Of Mir-24 In Cancermentioning
confidence: 99%